Протидія дезінформації під час російсько-української війни - Насібович, Валентина Валеріївна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The Russian-Ukrainian war is one of the biggest disinformation campaigns in modern history. Misinformation can spread in a variety of ways, including social media, traditional media, and government propaganda channels. Disinformation is very effective because it can affect people’s emotions and undermine their trust in authoritative sources. During the Russian-Ukrainian war, the fight against disinformation became an important element of national security and stability. In this fight, it is important to combine technological, informational and sociocultural approaches to ensure effective countermeasures against disinformation and support the resilience of societies facing information warfare.